2022
DOI: 10.3389/fneur.2022.973163
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica spectrum disorder in Western China impacts employment and increases financial burden in women

Abstract: BackgroundNeuromyelitis optica spectrum disorder (NMOSD) often leads to disability and exerts a heavy toll on the work and life of affected female patients. This study aimed to analyze the current employment situation and economic burden as well as the risk factors for unemployment in female patients with NMSOD.MethodsWe compared the following unemployment- and employment-related aspects in with NSMOD, which were investigated using questionnaires: the specific impact of NMOSD on work, medical expenses, and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
2
0
0
Order By: Relevance
“…In Western China, Han et al recently studied 351 females with NMOSD, finding lower education (middle school or below), older age, higher annual disease recurrence rate, and severe disability were each predictors of unemployment. 17 Similar to our study, 54% of participants reported that NMOSD led to job loss. Education level was not a significant predictor of unemployment in our study; however, our cohort had less variation, since all except one participant in our cohort had completed high school, while 59% of participants in Han et al's study completed high school or above.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In Western China, Han et al recently studied 351 females with NMOSD, finding lower education (middle school or below), older age, higher annual disease recurrence rate, and severe disability were each predictors of unemployment. 17 Similar to our study, 54% of participants reported that NMOSD led to job loss. Education level was not a significant predictor of unemployment in our study; however, our cohort had less variation, since all except one participant in our cohort had completed high school, while 59% of participants in Han et al's study completed high school or above.…”
Section: Discussionsupporting
confidence: 87%
“…In Western China, Han et al. recently studied 351 females with NMOSD, finding lower education (middle school or below), older age, higher annual disease recurrence rate, and severe disability were each predictors of unemployment 17 . Similar to our study, 54% of participants reported that NMOSD led to job loss.…”
Section: Discussionsupporting
confidence: 87%